The efficacy of the antimicrobial peptides D4E1, VvAMP-1 and Snakin1 against the grapevine pathogen aster yellows phytoplasma - Spinas, Nicole Lotte (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.